Ultrafast capillary electrophoresis isolation of DNA aptamer for the PCR amplification-based small analyte sensing - Fiore, Emmanuelle; Dausse, Eric; Dubouchaud, Hervé; Peyrin, Eric; Ravelet, Corinne (Frontiers in Chemistry, 2015)
Here, we report a new homogeneous DNA amplification-based aptamer assay for small analyte sensing. The aptamer of adenosine chosen as the model analyte was split into two fragments able to assemble in the presence of target. Primers were introduced at extremities of one fragment in order to generate the amplifiable DNA component. The amount of amplifiable fragment was quantifiable by Real-Time Polymerase Chain Reaction (RT-PCR) amplification and directly reliable on adenosine concentration. This approach combines the very high separation efficiency and the homogeneous format (without immobilization) of capillary electrophoresis and the sensitivity of real time PCR amplification. An ultrafast isolation of target-bound split aptamer (60 s) was developed by designing a capillary electrophoresis input/ouput scheme. Such method was successfully applied to the determination of adenosine with a LOD of 1 µM.